EVALUATION OF WATERSHED PROJECTS USING REMOTE SENSING AND GIS TECHNOLOGIES IN Y.S.R. KADAPA DISTRICT OF ANDHRA PRADESH - P. VENKATARAM MUNI REDDY*, KONA SASIDHAR, C.P REDDY, R. V. SAGAR KUMAR REDDY; B. JANARDHAN REDDY (The Journal of Research ANGRAU, 2022)
The current study was undertaken to investigate the utility of Remote sensing and Geographic information system (GIS) tools for evaluation of seven watershed projects implemented under Pradhan Mantri Krishi Sinchayee Yojana (PMKSY) project during 2009-’16 in YSR Kadapa District of Andhra Pradesh. The study was carried out using high resolution Resourcesat-2, Linear Imaging Self-scanning Sensor (LISS)-IV data of 2011 (pre-treatment) and 2016 (post-treatment) to assess the changes in land use/land cover and biomass over a period of five years (2011-’16). Due to implementation of the watershed developmental activities, an additional area of 3618 ha has been brought under cultivation. The vegetation maps indicated that the areas under dense and open vegetation categories were increased from 2224 to 4915 ha and 5864 to 10670 ha during the project period due to adoption of soil and water conservation practices. An additional area of 191 ha (8.99%) increased under water bodies and 518 ha waste land was converted to cultivable land due to construction of farm ponds, percolation tanks and check dams. This area is attributed to cropland and plantations in the year 2016.